Двигательная активность – важнейшая проблема здорового образа жизни молодежи - Артыков, М.А.; Артыкова, Н.М. (My University, 2013)
The results of the researches which howe been carried out on students youth of the I,II, III, IV rates of the state pedagogical institute of Kostanay are given and generalized in this scientific work. They consider in this work the power and functional opportunities of students actively engaged into various physical training and sports sections and of students conducting a passive way of life. Researches have revealed high functionalities of an organism of the youth conducting an active and healthy way of life.